Significance of urinary isolates of coagulase-negative Micrococcaceae. - Williams, D N (1976)
Of 16,347 urine cultures submitted to the hospital laboratory, 68 (0.4%) specimens from 50 patients yielded greater than 10(4) coagulase-negative staphylococci/ml in pure culture. A total of 62 of 63 organisms available for study were staphylococci: 45 Staphylococcus epidermidis (predominantly subgroup 1), 15 Staphylococcus saprophyticus (subgroup 3), and 2 Staphylococcus aureus. Twenty-one patients had "probable" urine infections. Eight patients had two or more positive urine cultures, and all isolates from the same patients were identical (by morphology, antibiotic susceptibility, and hemolytic pattern). Nine (75%) of the 12 isolates of S. saprophyticus, which were novobiocin resistant and nonhemolytic on the synergistic hemolysis test, were from patients with probable urinary infection. Eight were young women with acute symptoms and pyuria. Differences in the glucose and mannitol fermentation tests with different media may lead to difficulties in identification. Novobiocin resistance cannot be relied upon to differentiate isolates of S. saprophyticus from S. epidermidis.